The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jbi.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pivotal experiences in behavior change for the design of technologies for personal wellbeing

Abstract: Most health technologies are designed to support people who have already decided to work toward better health. Thus, there remains an opportunity to design technologies to help motivate people who have not yet decided to make a change. Understanding the experiences of people who have already started to make a health behavior change and how they made a pivotal decision can be useful in understanding how to design such tools. In this paper, we describe results from data collected in 2 phases. Phase 1 consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Indeed, there is evidence that pivotal experiences (such as LLA) may provide time windows of opportunity when people are open to health behavior changes. 61 Little is known regarding the influence of time since amputation on physical activity. A study of 72 people with LLA from various etiologies (35% nontraumatic, dysvascular) found lower self-reported physical activity to be weakly associated with shorter time since amputation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is evidence that pivotal experiences (such as LLA) may provide time windows of opportunity when people are open to health behavior changes. 61 Little is known regarding the influence of time since amputation on physical activity. A study of 72 people with LLA from various etiologies (35% nontraumatic, dysvascular) found lower self-reported physical activity to be weakly associated with shorter time since amputation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that people are more able or willing to change walking behaviors early after LLA compared to more than a year after LLA (as in the current trial). Indeed, there is evidence that pivotal experiences (such as LLA) may provide time windows of opportunity when people are open to health behavior changes …”
Section: Discussionmentioning
confidence: 99%
“…The contextual differences between the fields and the relationships with the game features and theories are articulated in the following sections. 'Challenges' was the most common game feature in health studies; this feature taps into players' tendency to accept challenges in order to onboard and engage, as this behaviour can motivate players to complete the game [54]. Various health studies employ games that apply challenge mechanics that influence players to do or stop certain habits when they play together [87].…”
Section: Discussionmentioning
confidence: 99%
“…Positive transformational experiences following trauma in the form of adversarial or post‐traumatic growth (PTG, Linley & Joseph, ) have received substantial attention in recent decades, and PTG could be said to have become the flagship theme of positive psychology (Joseph, ). Other terms have also been adopted in an attempt to capture the capacity of the human organism for profound and enduring positive change, including transformative change experiences, (White, ) unencumbered moments (Murray, ), turning points (Berglund, ), transformational growth (Ivtzan, Lomas, Hefferon, & Worth, ) and pivotal experiences (Bhattacharya et al., ). Common characteristics among these experiences have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%